(3JbQjH MUhd GdebGUOs - (3eUWai Hf YHO GdQMef GdGRejQis; (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3BNQgG (B:s
(3hSY eOJjf eO (B4 (3abW hGdbUQ eY bUQ hJSgjd SbW Hd hSW CeOO (B4 (3hhSWgG dOi eJhSW hHYO eO aGeOg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B291s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1953s
Keywords: (3GdbQGAGJ hGdJLhjOs